Tingkat Penerimaan Panelis dan Kandungan Gizi Waffle dengan Penambahan Pasta Tomat - Agnes Bili; Ira Handayani; Ndaru Prasastono (Garina, 2024)
Tomatoes are one of the alternatives used to make tomato paste, which can be added to waffle preparation to enhance their flavor. Innovation is needed to create new products and increase the utilization of local food ingredients with economic value. The objectives of the research are: 1) To determine the public acceptance of waffles with added tomato paste, 2) To identify the best recipe for waffles with added tomato paste, and 3) To analyze the carbohydrate and fat content in waffles with added tomato paste. The experimental method involved formulating waffle recipes with varying percentages of tomato paste addition: 15%, 30%, and 45%. A total of 35 panelists participated in this study. The research results were analyzed using descriptive analysis. The findings showed that waffles with 45% tomato paste addition were the most preferred and accepted by the panelists. The most accepted waffle composition included: 130 g of wheat flour, 58 g of tomato paste, 50 g of eggs, 40 g of sugar, 190 ml of UHT milk, 3 g of baking powder, and 60 g of margarine. The nutritional value per 100 g of the best tomato paste waffle is 43.01% carbohydrates and 5.889% fat.